2019
DOI: 10.3892/ijmm.2019.4072
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin protects against uric acid‑induced renal tubular epithelial inflammatory responses via the AdipoR1/AMPK signaling pathway

Abstract: Adiponectin (APN) exerts anti-inflammatory effects in various cells. Uric acid (UA) induces inflammation in proximal renal tubular epithelial cells (PTEcs). It remains unknown whether APN protects against UA-induced inflammation. In the present study, human PTEcs were incubated with 100 µg/ml soluble (S) UA in the presence or absence of globular (g) APN, APN receptor 1 (AdipoR1)-short hairpin RNA lentivirus or compound c. Reverse transcription-quantitative polymerase chain reaction (RT-qPcR) assays were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…[711] In addition, the suppressive effects of adiponectin on TNF-α production have been confirmed in uric acid-insulted renal tubular epithelial cells, LPS-stimulated cardiomyocytes, and palmitic acid-exposed endothelial. [11,22,23] In the present study, LPS/D-Gal-induced production of TNF-α was suppressed by AdipoRon, which might contribute greatly to the beneficial outcomes in AdipoRon-treated animals.…”
Section: Discussionmentioning
confidence: 48%
“…[711] In addition, the suppressive effects of adiponectin on TNF-α production have been confirmed in uric acid-insulted renal tubular epithelial cells, LPS-stimulated cardiomyocytes, and palmitic acid-exposed endothelial. [11,22,23] In the present study, LPS/D-Gal-induced production of TNF-α was suppressed by AdipoRon, which might contribute greatly to the beneficial outcomes in AdipoRon-treated animals.…”
Section: Discussionmentioning
confidence: 48%
“…We have previously demonstrated that the impairment of NKA function is one of the pivotal steps in HUA-induced renal tubular injury 6 and that AMPK activation is observed in HUA-induced renal tubular injury 23 . In our present study, we further noted that AMPK activation significantly increased NKA activity by restoring NKA cell surface expression following AICAR treatment, whereas the AMPK inhibitor Comp C exerted the opposite effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, soluble UA activated NLRP3 inflammasome to secrete IL-1 β in macrophages and stimulated the release of CXCL12 and HMGB1 in TECs, while interaction between macrophages and TECs promoting the progression of DN [ 108 ]. Soluble UA significantly enhanced NLRP3, tumor necrosis factor- (TNF-) α as well as IL-1 β in TECs, while AMP-activated protein kinase (AMPK) exerted a protective effect on UA-induced inflammatory response [ 120 ]. In the absence of lysosomal ruptures, mitochondria-derived ROS may mediate soluble UA-activated NLRP3 inflammasome [ 119 ].…”
Section: Mechanisms Of Hyperuricemia-induced Renal Injurymentioning
confidence: 99%